Effects of a short-term fast on albumin synthesis studied in vivo, in the perfused liver, and on amino acid incorporation by hepatic microsomes - Rothschild, Marcus A. (1968)
Carbonate-(14)C was used to label the hepatic intracellular arginine pool and direct measurement of albumin synthesis was made in six rabbits before and after an 18-36 hr fast. 18 perfusion studies were performed with livers derived from fed and fasted rabbits (18-24 hr). Microsomal amino acid-incorporating ability with leucine-(3)H and phenylalanine-(14)C was compared in 17 studies, using microsomes isolated from livers taken from fed and fasted rabbits and from isolated perfused livers whose donors were fed and fasted. Albumin synthesis is rapidly inhibited by fasting. Albumin synthesis decreased 33% in vivo and 53% in the perfused liver. The microsomes from perfused livers taken from fed animals did not demonstrate a significantly reduced capacity to incorporate leucine-(3)H or phenylalanine-(14)C into protein. Microsomes derived from perfused and nonperfused livers whose donors were fasted incorporated 32-54% less tracer than microsomes obtained from fed donor rabbits. Microsomes separated from perfused livers removed from fed and fasted rabbits responded to polyuridylic acid stimulation and phenylalanine-(14)C incorporation rose from 58 to 171%. An 18-36 hr fast inhibits albumin production in vivo and in the perfused liver. The microsomal system is less active in the fasted state and perfusion per se does not inhibit the microsomal response.